2011
DOI: 10.1103/physrevlett.106.224301
|View full text |Cite
|
Sign up to set email alerts
|

Wrinkling Hierarchy in Constrained Thin Sheets from Suspended Graphene to Curtains

Abstract: We show that thin sheets under boundary confinement spontaneously generate a universal self-similar hierarchy of wrinkles. From simple geometry arguments and energy scalings, we develop a formalism based on wrinklons, the localized transition zone in the merging of two wrinkles, as building blocks of the global pattern. Contrary to the case of crumpled paper where elastic energy is focused, this transition is described as smooth in agreement with a recent numerical work [R. D. Schroll, E. Katifori, and B. Davi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
189
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(204 citation statements)
references
References 24 publications
15
189
0
Order By: Relevance
“…Thus, H 1 encapsulates bending and splaying of wrinkles beyond those prescribed by the asymptotic stress field through aðxÞ. The specific form of H 1 remains unknown, despite some recent works that addressed the energetic cost associated with smooth and sharp transformations of n wrinkles to n + m wrinkles (17,18,25). However, the unexpectedly good agreement obtained between the simple local λ law and experiments suggests that, in circumstances that remain to be understood, the effect of H 1 may safely be neglected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, H 1 encapsulates bending and splaying of wrinkles beyond those prescribed by the asymptotic stress field through aðxÞ. The specific form of H 1 remains unknown, despite some recent works that addressed the energetic cost associated with smooth and sharp transformations of n wrinkles to n + m wrinkles (17,18,25). However, the unexpectedly good agreement obtained between the simple local λ law and experiments suggests that, in circumstances that remain to be understood, the effect of H 1 may safely be neglected.…”
Section: Discussionmentioning
confidence: 99%
“…4C presents data from large sheets; here the edge fell outside the illuminated region, so the edge cascade was not visible). The local effect of the liquid meniscus or other boundary forces (18,(28)(29)(30) are not accounted for in Eqs. 1 and 2.…”
Section: Indentation Of a Floating Sheetmentioning
confidence: 99%
“…Furthermore, in both cases, the subdominant energies consist of a mixture of stretching and bending terms that determine small-scale features of the pattern: wavelength (wrinkling) and the size of stress-focusing zones (crumpling). Recent experiments (23,24) have shown that this mixture of subdominant energies leads to the complex shapes of curtains: multiscale, hierarchical patterns that interpolate between crumpling-and wrinkling-like shapes.…”
Section: Discussionmentioning
confidence: 99%
“…In order to study carefully the properties of the emerging structures, we focus on bilayer systems compressed uniaxially in the plane of the rigid membrane that have been intensively studied. [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63] Notice, however, that more complex geometries have already been studied by considering biaxial/radial stresses (with or without substrate) or curved substrates [64][65][66][67][68][69][70][71] where wrinkle to fold transitions can also be observed for large enough deformations of the systems.…”
Section: -47mentioning
confidence: 99%